Horse in the Palaeometal era cultures of the Minusinsk basin - Poliakov Andrei V. (Поволжская археология)
The article presents modern data on the stages of development of horse use by man in the Palaeometal epoch on the example of archaeological sites of the Minusinsk basin. The beginning was made in the Afanasievo era and can probably be considered as periodic domestication or early stages of domestication. In the Okunev culture, the first experiments in training and wider use of horses are already taking place. The Andronovo culture and the early stages of the Karasuk period demonstrate the use of the horse as a draft animal in light carts and chariots. Finally, the end of the Palaeometal epoch is characterized by horseback riding, which had a very significant impact on the entire economic life of steppe pastoralists.